Who Is Responsible for Today’s Northern Landscapes, Climate or Human Beings? - Hicks, Sheila (Journal of Northern Studies, 2014)
The present-day landscapes of northern Fennoscandia are the end result of a process of evolution. Mountains and valleys have scarcely altered during the last 10,000 years, whereas coastal areas have slowly but constantly changed. The nature of the vegetation that covers the landscape and is driven primarily by climate, has changed at a faster rate, but fastest of all have been the changes resulting from human activities. Steps towards the present-day situation are briefly reviewed on different temporal and spatial scales and on each the impacts of climate and people are weighed one against the other. Environmental reconstructions are made on the basis of pollen analysis and historical/archaeological records, while a quantified basis for their interpretation is provided by present day reference situations. Examples from palaeoecological research projects provide illustrations. On the coarsest spatial and temporal scales the bigger driving force is climate, but if the focus is on a small area and the time considered the last 100 years, then it is people who have played the bigger role in producing what we see. Two important questions for the north are: which impact will have the bigger effect in the future, the climate or human beings, and will future changes be reversible or not?